Take advantage of Vive Digital Plus Points through of mediation of ICT with B_Learning modalit - Cruz Mesa, Yerson Jaime; Chanchí Golondrino, Gabriel Elías; Velarde Bedregal, Héctor Raúl (I+ T+ C- Research, Technology and Science, 2018)
One of the most important challenges facing the community of educators in this new digital era is to acquire new concepts on the management and inclusion of learning methods through mediation of Information and Communication Technologies. This process will focus on structuring a guide to improve the pedagogical practices of administrators in Live Digital Plus Points (L.D.P.P.); to begin with, the role changes in the teachers and students that this new digital era has brought will be deducted; at the same time read the digital environment, encompassing several actions, such as identifying, recognizing and understanding digital characteristics, thus achieving an effective mediation in the didactic triangle, teacher, content, student, through the B-Learning modality as one of the trends in education with more boom worldwide, for combining digital media in line with traditional methods of the classroom. There are different models of B-Learning however we will be guided by the Face to Face Driver model: where the teacher promotes instruction and promotes knowledge management through the mediation of ICT